Azacitidine, intensive chemotherapy or best supportive care in relapsed or refractory acute myeloid leukemia, a DATAML registry study. Issue 6 (12th May 2022) - Gadaud, Noémie; Leroy, Harmony; Bérard, Emilie; Tavitian, Suzanne; Leguay, Thibaut; Dimicoli-Salazar, Sophie; Rieu, Jean-Baptiste; Luquet, Isabelle; Largeaud, Laetitia; Bidet, Audrey; Delabesse, Eric; Klein, Emilie; et al.
Abstract: We analyzed 526 consecutive acute myeloid leukemia patients refractory to or relapsing after chemotherapy. 270 patients received intensive salvage chemotherapy (IC), 97 azacitidine (AZA) and 159 best supportive care (BSC). Complete response was obtained in 37/19/0% ( p  = .0008). Allogeneic stem-cell transplantation (alloSCT) was performed in 39.3/10.3/0%. Median overall survival (OS) and 5-year OS were 8.2/9.6/2.2 months and 16/6/2% ( p  < .0001). Predictive factors of worse OS were post-myelodysplastic/chronic myelomonocytic leukemia, bone marrow blasts ≥20%, adverse cytogenetics, AZA cycle ≥2 and no alloSCT at R/R for AZA and age, performance status, white blood cell count and myelodysplasia-related changes for IC. The impact of treatment was time-dependent: adjusted hazard ratio for OS was in favor of AZA up to 1 month, was not different between 1 and 7 months, then was in favor of IC after 7 months. While AZA represents a therapeutic option for the oldest patients, it does not lead to long-term survivors.